Do gaming motives mediate between psychiatric symptoms and problematic gaming? An empirical survey study. (3rd September 2017) - Ballabio, Matteo; Griffiths, Mark D.; Urbán, Róbert; Quartiroli, Alessandro; Demetrovics, Zsolt; Király, Orsolya
Abstract: Previous research has suggested that motives play an important role in several potentially addictive activities including online gaming. The aims of the present study were to (i) examine the mediation effect of different online gaming motives between psychiatric distress and problematic online gaming, and (ii) validate Italian versions of the Problematic Online Gaming Questionnaire, and the Motives for Online Gaming Questionnaire. Data collection took place online and targeted Italian-speaking online gamers active on popular Italian gaming forums, and/or Italian groups related to online games on social networking sites. The final sample size comprised 327 participants (mean age 23.1 years [SD = 7.0], 83.7% male). The two instruments showed good psychometric properties in the Italian sample. General psychiatric distress had both a significant direct effect on problematic online gaming and a significant indirect effect via two motives: escape and fantasy. Psychiatric symptoms are both directly and indirectly associated with problematic online gaming. Playing online games to escape and to avoid everyday problems appears to be a motivation associated with psychiatric distress and in predicting problematic gaming.